2019
DOI: 10.6004/jnccn.2018.7282
|View full text |Cite
|
Sign up to set email alerts
|

Do Outcomes in Elective Colon and Rectal Cancer Surgery Differ by Weekday? An Observational Study Using Data From the Dutch ColoRectal Audit

Abstract: Background: Previous studies showing higher mortality after elective surgery performed on a Friday were based on administrative data, known for insufficient case-mix adjustment. The goal of this study was to investigate the risk of adverse events for patients with colon and rectal cancer by day of elective surgery using clinical data from the Dutch ColoRectal Audit. Patients and Methods: Prospectively collected data from the 2012–2015 Dutch ColoRectal Audit (n=36,616) were used to examine differences in mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…In contrast, the crude 30-day mortality for elective colorectal (colon and rectum) surgery in previous studies was approximately 2.2%-3.5%. 6,22,23,24 The low frequency of events (death) could have simply impeded the detection of a small difference in mortality between days of the week despite the large sample size in the present study.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In contrast, the crude 30-day mortality for elective colorectal (colon and rectum) surgery in previous studies was approximately 2.2%-3.5%. 6,22,23,24 The low frequency of events (death) could have simply impeded the detection of a small difference in mortality between days of the week despite the large sample size in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, the present study is the first large-scale study investigating the effect of the day of the week on mortality focusing on elective right hemicolectomy for colon cancer instead of using a heterogenous group of patients. [22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Njjolstad [32] found that surgical treatment of endometrial cancers later in the week was associated with worse outcomes. In contrast, Huijts [33] and Frostberg [34] found no evidence of weekday effect in patients undergoing elective surgery for colon or rectal cancer. Similarly, Visser [35] found no difference in immediate or longterm outcomes after gastrectomy done earlier versus later in the week.…”
Section: Discussionmentioning
confidence: 97%
“…This observation hints at a potential systematic phenomenon tied to operational practices within healthcare settings. However, this ‘weekday effect’ hypothesis is not unanimously supported as other studies found no significant impact of the day of the week on the outcomes of elective oncological resections 6 8 . This discrepancy in findings could be attributed to variations in healthcare systems between countries, differences in study design, or disparities in the clinical conditions being studied.…”
Section: Introductionmentioning
confidence: 90%